Augmented Reality–Assisted PDEODE Instruction for Reducing Misconceptions in Momentum and Impulse - Wulandari, Novia; Agustine, Eleonora; Febriandirza, Arafat; Prakasa, Esa (Syntax Corporation, 2026)
Misconceptions remain a persistent challenge in physics learning, particularly in the topics of momentum and impulse, which may hinder students’ understanding of subsequent physics concepts and problem-solving abilities. This study investigates the effect of implementing Augmented Reality–Assisted Instruction integrated with the PDEODE learning strategy on reducing students’ misconceptions regarding momentum and impulse. The research employed a mixed-method approach using an embedded mixed- method design to obtain both quantitative and qualitative insights. The instruments used included a Four-Tier Momentum and Impulse diagnostic test (FOTMI), Augmented Reality–based student worksheets, and observation sheets for monitoring the implementation of learning activities. The participants consisted of 30 eleventh-grade students (7 male and 23 female) from a public senior high school in Central Java. The effectiveness of the AR- assisted PDEODE strategy was analyzed using Cohen’s d effect size, while the learning implementation was evaluated in percentage form to determine its feasibility and consistency. The findings indicate a reduction in students’ misconceptions from 37.7% in the pretest to 33.5% in the posttest, reflecting a decrease of 4.2%. Furthermore, the analysis of conceptual change revealed that 32% of students experienced Accepted Change (AC), 44% showed No Change (NC), and 25% demonstrated Unacceptable Change (UC). These results suggest that the integration of Augmented Reality with the PDEODE strategy has the potential to support conceptual understanding, although further refinement is needed to optimize learning outcomes.